Identification and IDNs in the Metaverse: who will we be? - Haahr, Mads (Springer, 2022)
One’s digital identity on the Metaverse is critical enough to warrant EU regulation. Suggesting Interactive Digital Narratives as having a role to play in the Metaverse, we focus on the identity of the Virtual Reality interactor in such virtual spaces, and the potential impact this may have on the self-identity of the interactor. Building upon the notions of identity and the interactor’s construction of their narrative identity, we revisit identification in the context of VR Interac- tive Narratives (VRINs) and explore authenticity and character similarity as its dimensions. We interpret the construction of a narrative identity in VR as a vehicle for identity shift between the interactor’s self-identity and identification with the character. Based on the theoretical framework, we present a conceptual model for identity shift in VRINs which we then apply to a number of case studies to exemplify its utility and provide some guidelines for VRIN authors in how to use this model.
Lecture Notes in Computer Science
International Conference for Interactive Digital Narrative (ICIDS 2022)
PUBLISHED
Santa Cruz, CA, USA
Keywords: Virtual reality, Interactive narrative, Identity, Authenticity